Clinicopathological findings and risk factors associated with Cytauxzoon spp. infection in cats: A case-control study (2008–2021) - Carli, Erika; Solano-Gallego, Laia; De Arcangeli, Stefano; Ventura, Laura; Ligorio, Elisa; Furlanello, Tommaso (Frontiers in Veterinary Science, 2022)
In Europe, Cytauxzoon spp. infection was documented in domestic and wild felids. Cats often develop a subclinical infection, while fatal disease is rare. Currently, information on the epidemiology, risk factors and clinicopathological findings of Cytauxzoon spp. infection remains limited and obtained by a single subject or small groups of cats. The objective of this case-control study was to evaluate clinicopathological findings and to describe risk factors associated with Cytauxzoon spp. infection in domestic cats. Infected cats (n=39) and non-infected (n=190) cats were selected from the database of the referral San Marco Veterinary Laboratory between 2008 and 2021. Demographic information, a preset questionnaire considering lifestyle, environment, and clinical status, and a CBC performed contextually with the PCR analysis were recorded for all cats. Data on the biochemical profile and serum protein electrophoresis were also evaluated when available. Compared to the control group, infection was more likely to occur in stray cats (24/39, 61.5%, P<0.001), living totally/partially outdoors (36/39, 92.3%, P<0.001), in an urban context (37/39, 94.9%, P=0.002), taken or recently adopted from colonies (34/35, 97.1, P<0.001), with irregular or absent parasite preventive treatments (39/39, 100%, p=0.005), without fleas (28/35, 80%, P=0.047) and without clinical signs (22/39, 56.4%, p=0.026) at the time of medical evaluation. Anemia was not associated with infection, but in cats without clinical signs, the percentage of anemic-infected cats (7/22, 31.8%, P=0.009) was higher compared to non-infected cats (5/65, 7.7%). Furthermore, a decrease in total iron serum concentration approximating the lowest reference interval [median values (IQR): 79 µg/dL (52.25) vs. 50.5 µg/dL (34), P=0.007] was likely in infected cats. No other laboratory findings were associated with infection. Interestingly, a partial/total outdoor lifestyle was a risk factor for infection (OR: 8.58, 95% CI: 2.90-37.0, P<0.001). In conclusion, the present study revealed that Cytauxzoon spp. infection manifests itself prevalently as a subclinical infection, based on physical examination and laboratory findings, in domestic European cats. However, subclinical infected cats were more likely to be anemic compared to non-infected.